2021
DOI: 10.1101/2021.01.25.21250315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-sectional survey of the workplace factors contributing to symptoms of anxiety and depression among nurses and physicians during the first wave of COVID-19 pandemic in two US healthcare systems

Abstract: BackgroundAnxiety and depression among physicians and nurses during COVID-19 pandemic in the USA is not well described and its modifiable causes poorly understood.MethodsWe conducted a cross-sectional survey of symptoms of anxiety and depression (Hospital Anxiety and Depression Scale) among physicians and nurses in two US healthcare systems June-Sept 2020. We ascertained features of work as well as its perceptions and associated concerns in relation to risk of anxiety and depression, while controlling for heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Having supportive "inner circle" of family, neighbours, and religious community appeared to be protective. Our findings largely agree with our in-depth look at sub-sample of our respondents who worked during the epidemic [9], within sub-sample who did not (S1 Table ), and in related work among healthcare workers done using similar instruments at a roughly the same time in Philadelphia [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Having supportive "inner circle" of family, neighbours, and religious community appeared to be protective. Our findings largely agree with our in-depth look at sub-sample of our respondents who worked during the epidemic [9], within sub-sample who did not (S1 Table ), and in related work among healthcare workers done using similar instruments at a roughly the same time in Philadelphia [10].…”
Section: Discussionsupporting
confidence: 87%
“…We reported that anxiety and depression in general population of Philadelphia during the first wave of the pandemic can be due to widespread disruption of working lives, especially in “non-essential” low-income industries, on par with experience in healthcare [ 9 ]. We verified that levels of anxiety and depression were indeed on par with healthcare setting through a survey of physicians and nurses that gathered data using analogous instruments at the same time in the same region [ 10 ]. We now turn our attention to broader range of experiences of persons in our sample that transcend work-related circumstances.…”
Section: Introductionmentioning
confidence: 78%
“…Having supportive “inner circle” of family, neighbours, and religious community appeared to be protective. Our findings largely agree with our in-depth look at sub-sample of our respondents who worked during the epidemic [9], within sub-sample who did not ( Table in S1 Table ), and in related work among healthcare workers done using similar instruments at a roughly the same time in Philadelphia [10].…”
Section: Discussionsupporting
confidence: 85%
“…An interesting finding unique to nurses, was that in addition to perceived safety concerns, distress was also predicted by additional elements such as lower levels of religiosity, older age, and degree of self‐efficacy. With regard to religiosity, previous literature suggests that religion can offer protection against psychological morbidity (Allen et al, 2008; Burstyn & Holt, 2021; Papazisis et al, 2014; Vasegh & Mohammadi, 2007). In an ongoing disaster such as the current pandemic, individuals may feel a loss of control and autonomy whereby religion may provide individuals with a coping mechanism to accept such changing circumstances (Burstyn & Holt, 2021; Zoellner & Maercker, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to religiosity, previous literature suggests that religion can offer protection against psychological morbidity (Allen et al, 2008; Burstyn & Holt, 2021; Papazisis et al, 2014; Vasegh & Mohammadi, 2007). In an ongoing disaster such as the current pandemic, individuals may feel a loss of control and autonomy whereby religion may provide individuals with a coping mechanism to accept such changing circumstances (Burstyn & Holt, 2021; Zoellner & Maercker, 2006). Our finding that older age in nurses increases the risk of distress is inconsistent with other studies (Moitra et al, 2021), however it may be derived from the increased vulnerability to severe illness from COVID‐19 as age increases (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%